2018
DOI: 10.1371/journal.pone.0203628
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal anthropometry of children and adolescents using 3D-body scanning

Abstract: 3D-body scanning anthropometry is a suitable method for characterization of physiological development of children and adolescents, and for understanding onset and progression of disorders like overweight and obesity. Here we present a novel body typing approach to describe and to interpret longitudinal 3D-body scanning data of more than 800 children and adolescents measured in up to four follow-ups in intervals of 1 year, referring to an age range between 6 and 18 years. We analyzed transitions between body ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The mounting rates of obesity and consequently obesity related diseases including diabetes, cardiovascular complications, metabolic disease, and specific types of cancer present a multifaceted health problem attributed primarily to health practices initiated during youth and adolescence [ 1 , 2 ]. According to reports from the 1999 to 2016 Nutritional Health and Examination Survey (NHANES), approximately one fourth of children in the United States between the ages of 2 and 19 years were classified as obese.…”
Section: Introductionmentioning
confidence: 99%
“…The mounting rates of obesity and consequently obesity related diseases including diabetes, cardiovascular complications, metabolic disease, and specific types of cancer present a multifaceted health problem attributed primarily to health practices initiated during youth and adolescence [ 1 , 2 ]. According to reports from the 1999 to 2016 Nutritional Health and Examination Survey (NHANES), approximately one fourth of children in the United States between the ages of 2 and 19 years were classified as obese.…”
Section: Introductionmentioning
confidence: 99%
“…Detecting excess adiposity at a young age is critical for preventing obesity and its many consequences later in life. In a recent longitudinal study of children aged 6 to 18 years, Loeffler‐Wirth et al reported that over 4 years only 3% of children with normal weight and underweight arrived at overweight status, and only 2% of children with overweight arrived at a normal weight. These findings suggest that children with overweight or obesity will likely stay that way as they reach adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Using eye-safe laser technology, three-dimensional images are designed within a few seconds in a double-triangulation process. The images are generated in AnthroScan 2.9.9 software, which, like the scanner itself, conforms to the international standard ISO 20685 [20]. The images can also be edited in the software.…”
Section: Three-dimensional (3d) Body Scanmentioning
confidence: 99%